Resistivity Measurements on Germanium for Transistors - Valdes, L. B. (Proceedings of the IRE, 1954)
This paper discusses a laboratory method which has been found very useful for measuring the resistivity of the semiconductor germanium. The method consists of placing four probes that make contact along a line on the surface of the material. Current is passed through the outer pair of probes and the floating potential is measured across the inner pair. There are seven cases considered, the probes on a semi-infinite volume of semiconductor material and the probes near six different types of boundaries. Formulas and curves needed to compute resistivity are given for each case.